The comparison of sensitivity and specificity of the critical care pain observation tool (CPOT) and behavioral pain scale (BPS): a scoping review - Ismail, Suhartini; Dortheis, Uniplaita Eper (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Assessing pain in critically ill patients receiving mechanical ventilatory support remains a challenge in the intensive care unit. Due to mechanical ventilation and a reduced level of consciousness, the patient was unable to verbally report perceived pain. Highly sensitive pain assessment tools are critical for pain detection in critically ill patients in the intensive care unit. The Critical Care Pain Observation Tool (CPOT) and the Behavioral Pain Scale (BPS) are two pain assessment tools recommended for use in the critical care settingObjective: The purpose of this study was to compare the sensitivity and specificity of CPOT and BPS in the assessment of pain in patients receiving mechanical ventilation.Methods: This study was a systematic review conducted using the Scopus, PubMed, ProQuest, and ScienceDirect databases and followed established guidelines for conducting systematic reviews or scoping reviewsResults: CPOT was found to be more sensitive at 95% with a cut-off score >2, whereas BPS exhibited higher specificity at 91.5% with a cut-off score >6Conclusion: Both CPOT and BPS demonstrate sensitivity to painful situations and are capable of detecting pain in critically ill patients.